The Effect of Net Profit Margin and Return on Equity Toward Profit Growth - Novia Handayani; Srihadi Winarningsih (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Abstract  - Profit Growth is one thing that is very important in many ways. Both for the benefit of the country and for the benefit of a company. To see the financial condition of a company, we can see it from the profit generated by the company. For this reason, this research was conduted to determine a relation between NPM and ROE toward Profit Growth on Food and Beverage company listed on Indonesia Stock Exchange period 2016-2019.  The population in this study were 26 Food and Beverage company listed on Indonesia Stock Exchange in the 2016-2019 period while the sample was 16 Food and Beverage company listed on IDX. Based on the result, the test of simultaneously result with the statistical test show that the variable NPM and ROE simultaneously affect the Profit Growth. Partially, NPM has an influence toward Profit Growth and ROE has an influence toward Profit Growth. The magnitude of the effect of the predictor variable using the coefficient of determination as much as 41,3% while the remainig 58,7% is influenced by other variables outside this research model. Keywords: Net Profit Margin (NPM), Return On Equity (ROE), Profit Growth